The effect of the Iraqi marshes environment on the works of artist Mahoud Ahmed: محمود حسين عبد الرحمن حسين (Al-Academy, 2020)
Scientific research on the environment of the Iraqi marshes, its beauty and its characteristics is considered one of the most important functions of Iraqi universities and scientific institutions, because of its great historical impact related to the identity of Iraq and the Iraqis and the basis of science and science, through which the first letter and the first human civilizations were established and in the same importance technical research is among the most important functions of departments Institutes and colleges of the arts, research centers and museums inside and outside Iraq. Also, research centers specialized in the natural environment of Iraq, including the marshes. Therefore, it is hoped that this research will develop the artistic field and its intimate relationship with the marsh environment in all aspects, especially in light of the modern concept of the marshes and its place in the list of the global human heritage, this concept in which knowledge is the main driver and the main motivation that motivated researchers to enter into it, especially When the researcher and artist are from this environment. The artist, Mahmoud Ahmed, embodies the environment of the marshes with timeless masterpieces that represent reality with absolute precision, but with his symbolic, realistic, expressive style. Without a doubt, the returns from this artistic research are numerous (aesthetic, social, historical and cultural). And its importance increases in developing the relationship between studying the marshes environment scientifically and technically and providing Iraqi, Arab and international libraries with modern and new knowledge about this relationship and to assist researchers in this regard by identifying the problems of this study and its most prominent solutions, results and conclusions. It was the most prominent problems of the study on the nature of the marshes environment, history and importance. And on the nature of the artist Mahood Ahmed (the marsh boy) and his spiritual relationship with this environment and its history. And about his style, topics and techniques in which he carried out his artistic achievements. The study was determined (1998-2002). The aim of the study was to show and highlight the impact of the Iraqi marshes environment on the works of artist Mahood Ahmed. With the applied axis that was represented by the research community and its specimens and analysis, the study came out with several results, including: The environment of the Iraqi marshes has an important place in the scientific, literary and artistic milieu, drawing from its rich history and its economic, political, social, military and cultural significance. Then the study was concluded with the most important sources on which it relied, then the appendices that specialized in a brief narration on the identity of the artist Mahood Ahmed and the identification of his scientific, literary and artistic achievements.